THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND COMPETENCE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE AT THE OFFICE OF TRANSPORTATION OFFICES AND PORT AUTHORITIES (KSOP) BATAM - Abdurr Rohmat; Angelina E Rumengan; Bambang Satriawan (Jurnal Ekonomi, 2022)
This study aims to examine the following five variables, Leadership Style, Organizational Culture, Competence, Job Satisfaction and Employee Performance. Data analysis with parametric and non-parametric statistics using SEM-PLS. The results of this study indicate a direct influence that Leadership Style and Competence have a positive and significant influence on Job Satisfaction of Batam Special KSOP Employees, Organizational Culture has a positive and insignificant effect on Job Satisfaction Batam Special KSOP Employees, Job Satisfaction, Organizational Culture and Competence have a positive and significant influence on Batam Special KSOP Employee Performance, Leadership Style has a positive and insignificant influence on Batam Special KSOP Employee Performance